Effects of Remote Working in Fortune 500 Global Companies - Andrés Jerónimo Arenas Falótico; Philipp Dernbach (AiBi Revista de Investigación, Administración e Ingeniería, 2022)
The 500 largest global companies are not just leaders economically, they are also seen as role models. Especially during Covid-19, they had to change their style of work. Most people were not allowed to work in the office anymore. For most people working at home was new to them. But different does not always mean worse. Considering the global companies as examples, they still require a set amount of time for purposes of adaptability. But especially after resolving the issues, people tend to be more productive and can generate greater output than originally expected. Every single company and individual are currently finding their optimal working condition. After the pandemic there will be a time where some colleagues prefer working totally remotely and others not. It will be a time where efficiency will not be measured by hours worked in office, however, rather on the quality of your work and the total output by each individual.